FORMULASI SOFT CHEWY COOKIES BEBAS GLUTEN DAN KASEIN BERBASIS KOMBINASI MOCAF DAN TEPUNG MILLET PUTIH UNTUK ANAK AUTISM SPECTRUM DISORDER Free Gluten and Free Casein Soft Chewy Cookies Formulation with Combination of MOCAF and White Millet Flour Based for Children with Autism Spectrum Disorder - Kirana Dwiyanti Prasetyo; Dominikus Raditya Atmaka (Universitas Airlangga, 2021)
Children with Autism Spectrum Disorder (ASD) have to eat a gluten-free casein-free diet due to their special condition. Casein is protein that contained in milk and milk-based product which are source of calcium. Their special condition make children with ASD have a low bone-mass than other children. Modifi ed Cassava Flour (MOCAF) and white millet fl our are free gluten food sources which have rich calcium that is needed to increase nutrient quality in soft chewy cookies. This study was aimed to determine the eff ect of MOCAF fl our and white millet fl our combination on acceptability and nutritional value of free gluten and free casein soft chewy cookies. This study was true experimental study with complete randomized design. This study used un-trained panelist including ASD children(7–11 years old (25 panelists) and their parents (25 panelists). There were 4 formulas in this study consisted of 1 control formula (F0) based on 100% wheat fl our, and 4 treatment formulas which were combination of MOCAF fl our and white millet fl our with a percentage ratio of combination F1 (0%:100%) ; F2 (50%:50%) ; and F3 (75%:25%). Kruskal Wallis statistical test results showed there were signifi cant diff erences of aroma, color, texture, and taste between each formula. Result of acceptability and nutritional value showed F3 as the best formula. Each 60 g soft chewy cookies F3 contains 176,4 mg of calcium which fulfi ll 18% of calcium adequacy for 7–11 year old children. Gluten-free casein-free soft chewy cookies with combination of MOCAF and white millet fl our are suitable as an alternative snack for ASD children.